2010
DOI: 10.1186/ar3116
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis in early rheumatoid arthritis: very early endothelial activation and rapid progression of intima media thickness

Abstract: IntroductionIn this study we aimed to investigate whether there are indications of premature atherosclerosis, as measured by endothelial dependent flow-mediated dilation (ED-FMD) and intima media thickness (IMT), in patients with very early RA, and to analyze its relation to biomarkers of endothelial dysfunction, taking inflammation and traditional cardiovascular disease (CVD) risk factors into account.MethodsPatients from the three northern counties of Sweden diagnosed with early RA are followed in an ongoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
132
3
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(146 citation statements)
references
References 37 publications
9
132
3
2
Order By: Relevance
“…Atherogenesis is a chronic inflammatory process of the arterial wall, finally leading to endothelial dysfunction [10,11], which involves the alteration of the control of the vascular tone, leukocytes trafficking and platelets adhesion. The risk of early onset of atherosclerosis is well known in individuals suffering from other chronic inflammatory disorders such as rheumatoid arthritis and systemic lupus erythematosus [12][13][14], thus it should not be surprising that, in the last decade, an increasing body of data, both epidemiological and clinical, have supported this association also in IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Atherogenesis is a chronic inflammatory process of the arterial wall, finally leading to endothelial dysfunction [10,11], which involves the alteration of the control of the vascular tone, leukocytes trafficking and platelets adhesion. The risk of early onset of atherosclerosis is well known in individuals suffering from other chronic inflammatory disorders such as rheumatoid arthritis and systemic lupus erythematosus [12][13][14], thus it should not be surprising that, in the last decade, an increasing body of data, both epidemiological and clinical, have supported this association also in IBD.…”
Section: Introductionmentioning
confidence: 99%
“…In adult populations with CID, indices of subclinical atherosclerosis have been well documented (10 -12) and related to worse cardiovascular prognosis (1,12). In patients with CID, vascular dysfunction appears to occur at a relatively young age (13,14). However, there are limited data on indices of premature atherosclerosis (15,16) in patients with JIA.…”
Section: Introductionmentioning
confidence: 99%
“…Further, inflammatory disorders, characterized by high levels of CRP, can develop a secondary immune cell activation, which may result in atherogenesis [54]. In addition, studies have demonstrated that inflammatory related markers such as lipoproteins, ox-LDLs [55], NO [55], TNF-a [56], RANKL [57], CD40L [58], IL-18 [59], MMP-9 [60], MCP-1 [61], insulin [45], EPCs [51] in atherosclerosis are altered in patients with RA. These evidences thus support the theory that systemic inflammation plays a crucial role in the pathogenesis of CVD in patients with RA.…”
Section: Chronic Inflammation and Immune Dysregulation Of Ra And Athementioning
confidence: 99%